The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/plants12030566
|View full text |Cite
|
Sign up to set email alerts
|

A Small Set of Nuclear Markers for Reliable Differentiation of the Two Closely Related Oak Species Quercus Robur and Q. Petraea

Abstract: Quercus robur and Q. petraea are, in addition to Fagus sylvatica, the main economically used deciduous tree species in Europe. Identification of these two species is crucial because they differ in their ecological demands. Because of a changing climate, foresters must know more than ever which species will perform better under given environmental conditions. The search for differentiating molecular markers between these two species has already lasted for decades. Until now, differentiation has only been possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In response to this challenge, molecular tools have been continuously improved, and a number of species marker kits have been developed and applied during the last decade (Guichoux et al 2011;Neophytou 2014;Reutimann et al 2020;Degen et al 2021;Schroeder and Kersten 2023). These methods have set new milestones for the delimitation of oak species, but their validity has been constrained by some biological and technical limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to this challenge, molecular tools have been continuously improved, and a number of species marker kits have been developed and applied during the last decade (Guichoux et al 2011;Neophytou 2014;Reutimann et al 2020;Degen et al 2021;Schroeder and Kersten 2023). These methods have set new milestones for the delimitation of oak species, but their validity has been constrained by some biological and technical limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier surveys (Scotti-Saintagne et al 2004;Reutimann et al 2020;Lesur et al 2018) in European white oaks indicated that such ideal cases rarely exist. However, some markers exhibit species frequency profiles close to the ideal case (so-called near-diagnostic SNPs, for example, an allele with a frequency larger than 0.9 in the target species, and alternate allele frequency larger than 0.9 in all other species) (Schroeder and Kersten 2023). Only a few of such markers would then be enough to assign trees to the correct species using appropriate analytical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier surveys (Scotti-Saintagne et al , 2004; Reutimann et al , 2020; Lesur et al , 2018) in European white oaks indicated that such ideal cases rarely exist. However, some markers exhibit species frequency profiles close to the ideal case (so-called near-diagnostic SNPs; for example an allele with a frequency larger than 0.9 in the target species, and alternate allele frequency larger than 0.9 in all other species) (Schroeder and Kersten, 2023). Only a few of such markers would then be enough to correctly assign trees to the correct species using appropriate analytical approaches.…”
Section: Introductionmentioning
confidence: 99%